3D Mapping and Simultaneous Navigation for Multi Micro Aerial Vehicles in Indoor Environments - Dilaver, Mustafa Burak; Cakmak, Furkan; Uslu, Erkan; Amasyali, M. Fatih; Yavuz, Sirma (IEEE, 2020)
One of the platforms that autonomous exploration applications can be used is micro aerial vehicles, which are used by robotic scientists, because of their high dynamic capabilities. A robot needs to do navigation in its surrounding environment to be able to do exploration. In outdoor and indoor environments with obstacles around, sensing an environment and creating its map to do navigation is a common practice in robotic studies. An aerial vehicle is able to reach to a target position without crashing into static and dynamic obstacles, with the help of costmaps created in navigation applications. To prevent an aerial vehicle, which is trying to find a path to a target position, from getting crashed into other vehicles in applications with multiple aerial vehicles, that aerial vehicle needs to take into account the paths that found by other vehicles. In this way it's possible to prevent aerial vehicles getting crashed into each other. In this work, a simultaneous navigation application is developed for aerial vehicles that can build concurrent 3D multi maps. Experiments have been done in Gazebo simulation environment of ROS framework.
Keywords: Micro aerial vehicles; multi mapping; navigation; path planning; Engineering; Telecommunications